A Systematised Review of Policy Responses to Supplier-Induced Demand - Mnguni, Lungelo (University of the Witwatersrand, Johannesburg, 2024)
Health systems around the world contend with cost containment. As a result, policymakers pay attention to how the use of health services drives health expenditure. The rate of use of health services can increase due to additional demand generated by healthcare providers. Currently, however, research on policy interventions used to address demand created by providers is limited. This paper therefore contributes to the literature by conducting a systematised review of common themes found in the literature on additional demand generated by healthcare providers, known as supplier-induced demand, and the associated policy interventions. Building on 33 papers identified in a 2019 scoping review by Mohammadshahi et al., a systematic search added 86 papers from PubMed and 134 from Scopus. After screening and applying inclusion and exclusion criteria, 11 articles were reviewed. This review identified four key themes in the research on supplier-induced demand: Competition, incentives, and responses to health reform, and responses to reimbursement changes. In addition, the study finds the focus areas of policy responses to supplier-induced demand to be the following: Provider payment methods, capacity management, stricter regulation and monitoring of adherence to clinical guidelines, increased reviews by insurers, and health promotion to patients. To allocate resources efficiently and equitably, health system leaders should strengthen the monitoring and evaluation of unintended consequences which stem from expanding access to health services.
A research report submitted in fulfillment of the requirements for the Master of Commerce, In the Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; supplier-induced demand; physician-induced demand; provider payment systems; healthcare utilisation; SDG-3: Good health and well-being